Relationship Between Mother's Knowledge Level and Toddler Massage Behavior at the Many Health Center, Kediri District - Endah Luqmanasari; Rofik Darmayanti; Betristasia Puspitasari (Sean Institute, 2025)
Infant massage is an important form of stimulation to support the growth and development of children. According to several studies, massage can help improve sleep quality, reduce colic, and strengthen emotional bonds between parents and children. In Indonesia, the practice of infant massage has become a common tradition, but understanding of the techniques and benefits still varies. Mothers' knowledge of infant massage is very important, because mothers are the primary caregivers who play a role in providing the stimulation needed by children. This study aims to analyze the relationship between the level of maternal knowledge and infant massage behavior at the Banyaka Health Center, Kediri Regency. The method used in this study was a survey with a cross-sectional design, involving 35 respondents who were mothers with toddlers. From the correlation analysis conducted, the results of the study showed that there was a significant positive correlation between the level of maternal knowledge and toddler massage behavior (p-value <0.05). Of the 35 respondents, around 60% of mothers had good knowledge of toddler massage, and among them, 75% routinely massaged their children. In contrast, only 30% of mothers with low knowledge did massage. The results of the study showed that there was a significant relationship between the level of maternal knowledge and toddler massage behavior. This study is expected to provide insight for health workers in improving education for mothers about the benefits of massage for toddlers.